2021
DOI: 10.12776/qip.v25i2.1596
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Innovation Capability: An Exploratory Study of Inclusive Leadership and Work Engagement

Abstract: Purpose: The purpose of this paper is to explore how innovation capability can be enhanced by inclusive leadership. In particular, the focus is on identifying the key drivers of work engagement and the role of leadership in boosting the innovation capability.            Methodology/Approach: This research has a qualitative exploratory nature. The exploratory fieldwork is based on an in-depth interview with the CEO, field observations and on the analysis of relevant corporate sources. Findings: The research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…5.1 Theoretical contributions First, academic discussions are increasingly interested in solutions to drive innovation to guarantee organizational success in the marketplace (Saunila, 2020;Le, 2021;Gui et al, 2022). Current literature exposes that research on antecedents and consequences of innovation is flourishing originated from its theoretical importance and practical relevance (Khan et al, 2019;Vladi c et al, 2021). However, what are the underlying factors that promote and nurture the development of both exploitative and exploratory innovation is still the big challenge and central question for firms in the management and strategy field (Khan et al, 2019;Lei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…5.1 Theoretical contributions First, academic discussions are increasingly interested in solutions to drive innovation to guarantee organizational success in the marketplace (Saunila, 2020;Le, 2021;Gui et al, 2022). Current literature exposes that research on antecedents and consequences of innovation is flourishing originated from its theoretical importance and practical relevance (Khan et al, 2019;Vladi c et al, 2021). However, what are the underlying factors that promote and nurture the development of both exploitative and exploratory innovation is still the big challenge and central question for firms in the management and strategy field (Khan et al, 2019;Lei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this study adds to the knowledge of KHRM practices from the theoretical lens of RBV and KBV to indicate that KHRM practices serve as key antecedents to foster the positive effects on KS behaviors and innovation. Current literature exposes that research on antecedents and consequences of innovation is flourishing originated from its theoretical importance and practical relevance (Khan et al , 2019; Vladić et al , 2021). However, what are the underlying factors that promote and nurture the development of both product and process innovation is still the big challenge and central question for firms in the management and strategy field (Yang et al , 2018; Le and Lei, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding is that our study revealed the effect of a specific leadership style, namely IL, on WFHI. This result can completely be explained based on the views of scholars that the openness, concern, support and sharing of leaders with IL will positively influence employees' work-related attitudes and behavioural intentions (Alang et al ., 2022; Choi et al ., 2015; Nguyen et al ., 2022; Vladić et al ., 2021; Zeng et al ., 2020). In addition, the mediating role of WFHRA in the relationship between IL and WFHI was also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, employees in organisations with leaders that adopt an IL style often feel engaged with their work. They also show a responsible attitude towards their work by being willing to exchange ideas and coordinate with leaders to find solutions to improve efficiency and productivity in any situation (Choi et al ., 2015; Nguyen et al ., 2022; Vladić et al ., 2021). IL also promotes employees' contributions to their organisations through the improvement of their workplace belongingness (Alang et al ., 2022; Katsaros, 2022) and encourages them to engage in decision-making, follow and implement their leaders' decisions, and change their participation attitude (Katsaros, 2022; Zeng et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%